Understanding “Good” and “Bad” Twitter Practices in Alternative Media: An Analysis of Online Political Media in the UK (2015–2018) - Richard Thomas (Journalism Practice, 2024)
Alternative Online Political Media (AOPM) have become increasingly important within international news landscapes, but their social media practices have received limited academic attention. Our large-scale content analysis (N = 14807) offers the first comprehensive study of how APOM in the UK use Twitter. Drawing on a pertinent model of social media use that enhances notions of “good” and “bad” journalism, and through our own sentiment analysis, we find Twitter norms closely aligned with those of legacy media, including a relatively limited online interaction with audiences. We conclude that while AOPM follow many social media logics consistent with mainstream news sites and add to the wider realm of political analysis, their highly partisan content means that their Twitter use cannot be considered balanced, neutral or objective.